Design and Development of A Web-Based Education Officers’ Mentoring Management System (EMMS) - Syazatul Natrah Abdul Rahman,; Hapini Awang,; Massudi Mahmuddin,; Nur Suhaili Mansor,; Nurul Farzana Anis Ahmad,; Pitri Yeni Azwa, (Multidisciplinary Applied Research and Innovation, 2023)
The Web-Based Education Officers’ Mentoring Management System (EMMS) is an online system that is developed specifically to manage information related to mentoring program of education officers and staffs in Pejabat Pendidikan Daerah Temerloh (PPDT), Pahang. The system allows its users, namely PPDT officers, administrative staff, mentees, and PPDT authorities to systematically record their activities during the mentoring program. To be specific, EMMS is intended to facilitate school-based mentoring activities by providing an online platform for PPDT officers in managing program information, allowing mentees to provide answers and feedback, and enabling the PPDT chief and the deputy chief education officers to monitor the program. The system is developed to improve the current manual record management that is not just costly, but also vulnerable to human errors. Based on the system prototyping development method, this project started by gathering the functional requirements through a series of meetings with the client. Next, the requirements are referred to design and develop the EMMS. Finally, a field study was done to see how well the prototype worked. The results of the evaluation show that EMMS is simple and easy to use. It is proved to be well-accepted by the respondents through its various useful features.